Characterizing the Right Ventricle: Advancing Our Knowledge - Chin, Kelly M.; Coghlan, Gerry (The American journal of cardiology, 2012)
Our ability to evaluate the right ventricle (RV) in pulmonary hypertension has traditionally been quite limited: the RV's complex anatomy is not adequately represented by 2-dimensional imaging, and our understanding of what is an adaptive and maladaptive RV response is incomplete. However, measures of RV function appear to be a strong predictor of survival in pulmonary hypertension. This is, therefore, a promising area for future study. To more fully understand the challenges and opportunities in this area, this article provides a review of RV embryology and anatomy, current assessment of the RV function, animal models of RV function, RV–pulmonary artery coupling, and how translating lessons from studies of the left ventricle may increase our knowledge of the RV.